The role of digital media legislation in combating hate speech on online platforms: Platform (X) as a case study (The International Journal of Educational Sciences and Arts, 2026)
This study aims to analyze the role of digital media regulations in combating hate speech on electronic platforms, with Platform X serving as a case study. It addresses the rapid transformations of the digital communication environment, where online platforms have expanded opportunities for expression, interaction, and public debate, while also creating spaces for the spread of incitement, discrimination, and exclusionary discourse. The study is grounded in a central research problem concerning the ability of current legislative and regulatory frameworks to keep pace with the borderless and fast-moving nature of digital communication, while regulating harmful content without undermining freedom of expression.The study adopts a descriptive-analytical approach through the analysis of relevant legal texts, digital media legislation, and previous studies. It also employs a questionnaire to measure users’ awareness of hate speech on Platform X and their knowledge of digital media regulations governing electronic content. The study is theoretically grounded in Social Responsibility Theory, which provides an appropriate framework for understanding the balance between media freedom and ethical and legal obligations toward society, particularly in relation to content that may threaten social peace and human dignity.The significance of this study lies in its focus on one of the most pressing issues in the digital media environment. It seeks to assess the effectiveness of digital media legislation in limiting hate speech and to identify the legal and technical challenges associated with applying such legislation to electronic platforms. The study also offers scholarly insights that may assist policymakers and regulatory bodies in developing more effective frameworks that balance user protection, freedom of expression, and the promotion of a responsible and safe digital communication environment.
Keywords: Digital Media Regulations; Hate Speech; Electronic Platforms; Platform X; Freedom of Expression; Social Responsibility; Digital Regulation; Legal Awareness